2016
DOI: 10.3892/ol.2016.5401
|View full text |Cite
|
Sign up to set email alerts
|

Sometimes it is better to wait: First Italian case of a newborn with transient abnormal myelopoiesis and a favorable prognosis

Abstract: Congenital leukemia is rare disease with an incidence of one to five cases per million births. Transient abnormal myelopoiesis (TAM), also called transient myeloproliferative disorder, is a pre-leukemia disorder that may occur in Down syndrome (DS) or non-DS infants. TAM may enter spontaneous remission; however, continual monitoring is required, as this disorder has been observed to develop into acute megakaryoblastic leukemia in 16–30% of cases. In the literature, 16 cases of TAM in non-DS infants have been r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…performed a literature review of 14 patients with TAM that was not associated with DS and reported that GATA1 mutations were analyzed in only eight patients, all of whom had GATA1 mutations as well as trisomy 21 in leukemic blasts, indicating that the biology of TAM without constitutional trisomy 21 was similar to that of TAM with constitutional trisomy 21/DS . After the report of Rozen et al., there have also been several case reports of TAM without constitutional trisomy 21 but harboring both trisomy 21 and GATA1 mutations in leukemic blasts . Here, we present the cytogenetic findings and GATA1 mutation status of a series of 17 patients with TAM and nonconstitutional trisomy 21 who had been tested for GATA1 mutations at a single institute.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…performed a literature review of 14 patients with TAM that was not associated with DS and reported that GATA1 mutations were analyzed in only eight patients, all of whom had GATA1 mutations as well as trisomy 21 in leukemic blasts, indicating that the biology of TAM without constitutional trisomy 21 was similar to that of TAM with constitutional trisomy 21/DS . After the report of Rozen et al., there have also been several case reports of TAM without constitutional trisomy 21 but harboring both trisomy 21 and GATA1 mutations in leukemic blasts . Here, we present the cytogenetic findings and GATA1 mutation status of a series of 17 patients with TAM and nonconstitutional trisomy 21 who had been tested for GATA1 mutations at a single institute.…”
Section: Discussionmentioning
confidence: 83%
“…19 After the report of Rozen et al, there have also been several case reports of TAM without constitutional trisomy 21 but harboring both trisomy 21 and GATA1 mutations in leukemic blasts. [21][22][23][24] Here, we present the cytogenetic findings and GATA1 mutation status of a series of 17 patients with TAM and nonconstitutional trisomy 21 who had been tested for GATA1 mutations at a single institute. All 17 patients harbored both trisomy 21 and GATA1 mutations in leukemic blasts, clearly showing that the molecular pathogenesis is common between TAM with and without constitutional trisomy 21.…”
Section: Discussionmentioning
confidence: 99%
“…A “watch and wait” approach with careful monitoring (including frequent physical examinations and blood counts) is necessary for CL with stable illness, because there is a possibility of SR without the use of chemotherapeutic medications that are associated with adverse effects[ 10 , 37 ]. According to the newly released guidelines, a low-dose cytarabine therapy is recommended for cases with multiorgan failure, high WBC counts (> 100 × 10 9 /L), hepatopathy, and other life-threatening diseases.…”
Section: Discussionmentioning
confidence: 99%
“…El gen GATA-1 es considerado como factor de riesgo de evolución a leucemia aguda, mientras que una leucocitosis superior a 100 000mm3, hepatomegalia e ictericia están directamente relacionados a mayor riesgo de mortalidad [20]. La adecuada evolución clínica y del recuento leucocitario del paciente descartó la presencia de una leucemia aguda congénita y soportan el diagnóstico de SMT; aunque en este paciente no se pudo realizar el estudio de la mutación (GATA-1).…”
Section: Discussionunclassified